Evolution and Research Trends in Physical Culture. A Longitudinal Analysis of Student Diploma Theses from the Didactic Team of Physical Culture Sciences, formerly the Department of Physical Culture, Faculty of Earth Sciences and Spatial Management, 2017-2024 - Magdalena Hagner-Derengowska; Anna Michalska; Radosław Muszkieta; Olga Smoleńska; Walery Zukow (Kazimierz Wielki University, 2024)
Objective: The aim of this study was to conduct a comprehensive analysis of diploma theses produced in the Department of Physical Culture at the Faculty of Earth Sciences and Spatial Management between 2017-2024, to identify main research trends, thematic evolution, and assess the impact of external factors on research directions in the field of physical culture. Material and Methods: The analysis included 95 diploma theses (82 bachelor's and 13 master's). Mixed research methods were applied, combining quantitative and qualitative analysis. Content analysis, statistical analysis (including chi-square tests, analysis of variance, linear regression), and advanced data analysis methods (LDA topic modeling, social network analysis, SARIMA time series analysis) were conducted. Additionally, measures of thematic diversity and supervisor specialization indicators were applied. Results: A statistically significant upward trend in the number of theses (β = 1.1875, p = 0.0134) and significant seasonality of defenses were found. Five main thematic areas were identified: physical activity and health (29.5%), tourism (23.2%), sport (21.1%), health (15.8%), and recreation (10.5%). LDA analysis revealed more detailed categories, indicating growing interdisciplinarity of research. A significant impact of the COVID-19 pandemic on thesis topics was observed in 2020-2021. Social network analysis showed a key role of certain supervisors in shaping research directions (highest eigenvector centrality = 1.00). Conclusions: The study revealed dynamic development of the physical culture discipline, with growing emphasis on interdisciplinarity and health aspects. Adaptation of research topics to current social and technological challenges was observed. Results indicate the need for further expansion of the thematic scope of theses, particularly in areas of new technologies and long-term effects of physical activity. The analysis provides valuable information for strategic planning of study program development and research directions in the field of physical culture, tourism, and recreation.